Monitoring the impact of COVID-19 in Myanmar: Mechanization service providers - June 2020 survey round - Takeshima, Hiroyuki; Win, Myat Thida; Masias, Ian (International Food Policy Research Institute, 2020)
Mechanization service providers in Myanmar were originally interviewed by telephone in early May 2020 in order to determine how their businesses were being affected by COVID-19 related restrictions. The results of that survey were published in Myanmar Strategy Support Program Policy Note 07. To trace the continuing impact of the COVID-19 pandemic on their economic activities, a second phone survey of mechanization service providers was done in mid-June 2020. This Policy Note reports on the results of this second survey.